Budaya Berhibur Menerusi Aplikasi Smule Dalam Karya Arca Instalasi - Omar, Aznan; Syed Abu Bakar, Syed Alwi; Muhammad, Mahizan Hijaz (Idealogy Journal; Vol 6 No 2 (2021): Idealogy Journal (September 2021), 2021)
This research project is an interpretation of a societal phenomenon in terms of the culture of using digital application for leisure and entertainment especially regarding the human behaviour and its obsession of using these applications in the social media platforms.  This idea was translated by using the idea of an installation of a fabricated sculpture.  The  idea of how the digital media plays a major role for leisure and its obsession was inspired by the artist Scott Snibbe. This reference includes on how netizens utilize and share their interests and interactions with these digital media, games and other kinds of digital media entertainments. The method used for this practical studio research are through self critical evaluation, studio experimentation and contextual reviews.  This research project was intended to contribute to the field of fine arts in terms of collecting symbolic visual narratives and its issues of the collective culture in regarding of leisure and entertainment and its popularity as a life style today.  With hope this research project will give a major impact in terms of understanding towards its trend and the digital entertainment itself.  The variation, the ever changing content of its application has impacted the popular culture itself through its spirit and behaviour, the wants and needs projected by the new expression of consumerism. Keywords Culture And Entertainment, Mobile Entertainment, Sculpture